2016
DOI: 10.1111/joac.12155
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Territories: Incomplete Enclosures and Agrarian Change on the Agricultural Frontier of Samlaut District, North‐West Cambodia

Abstract: In Cambodia, the interactions between large‐scale land investment and land titling gathered particular momentum in 2012–13, when the government initiated an unprecedented upland land titling programme in an attempt to address land tenure insecurity where large‐scale land investment overlaps with land appropriated by peasants. This paper is based on a spatially explicit ethnography of land rights conducted in the Samlaut district of north‐west Cambodia – a former Khmer Rouge resistance stronghold – in a context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The same patterns of boom and bust were experienced in Thailand (Sirisambhand, 1988) and at the global level across the Amazon deforestation frontier (Rodrigues et al, 2009). The livelihoods of smallholders, that had improved gradually over the period of agricultural expansion and intensification (Touk, 2004), have deteriorated in relation with heavy land degradation and yield declines (Martin et al, 2013;Montgomery et al, 2017;Touch et al, 2017), that led to indebtedness, asset de-possession, and labor migration to Thailand (Diepart & Sem, 2018).…”
Section: Discussion: Understanding and Influencing Pathways Of Land Umentioning
confidence: 91%
See 2 more Smart Citations
“…The same patterns of boom and bust were experienced in Thailand (Sirisambhand, 1988) and at the global level across the Amazon deforestation frontier (Rodrigues et al, 2009). The livelihoods of smallholders, that had improved gradually over the period of agricultural expansion and intensification (Touk, 2004), have deteriorated in relation with heavy land degradation and yield declines (Martin et al, 2013;Montgomery et al, 2017;Touch et al, 2017), that led to indebtedness, asset de-possession, and labor migration to Thailand (Diepart & Sem, 2018).…”
Section: Discussion: Understanding and Influencing Pathways Of Land Umentioning
confidence: 91%
“…Proximate (or direct) causes of land-use change constitute human activities or immediate actions that originate from intended land use and directly affect land cover, while underlying (or indirect, or root) driving forces are fundamental forces that underpin the more proximate causes of land-cover change (Lambin et al, 2003). Based on the literature review relevant to the agricultural expansion in the Northwest of Cambodia (Diepart & Dupuis, 2014;Diepart & Sem, 2015, 2018Montgomery et al, 2017;Touch, Martin, Scott, Cowie, & Liu, 2016, 2017, we identified three main categories of proximate causes: agricultural expansion and intensification, infrastructure development, and resources exploitation, and five main categories of underlying factors: political and institutional factors, economic factors, demographic factors, technological factors, and environmental factors (Fig. 1).…”
Section: Framing the Lucc Analysis: A Multi-scale Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The commercialisation of rice agriculture is now a national trend in Cambodia as farmers have become increasingly dependent on commodity markets (Beban & Gorman, ; Diepart & Sem, ; Mahanty & Milne, ). National government policy has contributed to this shift, as the government has actively promoted an export‐driven agricultural policy (RGC, ).…”
Section: Turning Land Into a Financial Assetmentioning
confidence: 99%
“…In particular, household debts have outpaced agricultural income: average microfinance loan sizes are now nearly three times larger than per capita income (Bylander, ). The majority of microfinance loans are instead repaid with wages, many of which are remitted from migrant family members (Bylander, ; Diepart & Sem, ). In Tiang's small hamlet, for instance, 14 out of 26 surveyed households rely on remittances to cover monthly loan repayments and other basic needs.…”
Section: Turning Land Into a Financial Assetmentioning
confidence: 99%